2017
DOI: 10.1002/dmrr.2960
|View full text |Cite
|
Sign up to set email alerts
|

Low triglyceride as a marker for increased risk of cardiovascular diseases in patients with long‐term type 2 diabetes: A cross‐sectional survey in China

Abstract: Whereas a high triglyceride level was associated with increased risk of CVD in short-term T2DM, low triglyceride was associated with increased CVD risk in long-term T2DM. Low triglyceride may be a marker of CVD risk in Chinese patients with long-term T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
1
7
1
Order By: Relevance
“…Secondly, the subgroup analyses on the impact of TG on CVD showed prominence among T2DM individuals with a mean age < 65 years. It is consistent with a recent cross-sectional study which found higher TG level was associated with an increased risk of CVD among the patients with short duration of diabetes, whereas, a lower TG level was associated with an increased risk of CVD in patients with longer duration of diabetes, and this association was mainly driven by CHD [34]. Older age tends to have a longer duration of diabetes in general.…”
Section: Discussionsupporting
confidence: 91%
“…Secondly, the subgroup analyses on the impact of TG on CVD showed prominence among T2DM individuals with a mean age < 65 years. It is consistent with a recent cross-sectional study which found higher TG level was associated with an increased risk of CVD among the patients with short duration of diabetes, whereas, a lower TG level was associated with an increased risk of CVD in patients with longer duration of diabetes, and this association was mainly driven by CHD [34]. Older age tends to have a longer duration of diabetes in general.…”
Section: Discussionsupporting
confidence: 91%
“…It is also well known that statins also have a triglyceride-lowering effect [ 83 ]. In a cross-sectional study of 223,612 patients with T2DM in China, researchers found that although lower triglyceride was associated with reduced CVD risk in the short-term, it was associated with increased risk in the long-term [ 84 ]. This paradox could mean that low triglyceride is not necessarily associated with good clinical outcomes in all people with T2DM and that there are subgroup associations with CVD in patients with different durations of T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with diabetes, hypertriglyceridemia plus low HDL-C levels were associated with a 2.13-fold greater HR and 95% CI (1.06 to 4.29) for stroke (P=0.060) when compared with those in individuals with P<0.001). 30 Moreover, hypertriglyceridemia is a risk factor for stroke irrespective of age. In a cross-sectional study on acute ischemic stroke (AIS) in children, hypertriglyceridemia was more common in children with arterial ischemic stroke than in those without stroke.…”
Section: Effects Of Triglycerides On the Risk Of Ischemic Strokementioning
confidence: 99%